Pembuatan Aplikasi Pembelajaran Huruf Dasar Hiragana dan Katakana Berbasis Android dengan Fitur Gesture Input dan Gesture Checking - Kurniawan, Malvin Yuwono; Andjarwirawan, Justinus; Yulia, Yulia (Jurnal Infra, 2015)
Rapidly increasing techonological development, especially in smartphone. In this time smartphone is a very popular device in all kinds of people from the young to the old. The same thing happened in education, especially in the study of foreign language. This thesis aims to combine the methods of learning foreign language with technology that can be reached by any ages and imporove the method of learning foreign language especially Japanese.This application is focused to leard the basic of Japanese language, which is Hiragana and Katakana. This application created for Android operating system by utilizing swipe feature that has been filtered to detect user input for the correct writing. Beside that, this application has games that can test and evaluate the ability of user.Based on testing of this application that can be concluded this application can run smoothly on Android JellyBean system until Lollipop.